El rol del idioma inglés en la comunicación interactiva entre Turista y Personal de servicio en el Hotel del Parque Guayaquil. - SANTILLAN MURILLO, ODALYS DAYANA (2024)
This study analyzes the importance of the English language in interactive communication between tourists and service personnel at the Hotel del Parque Guayaquil. In the methodology used, an exploratory study was carried out with a mixed approach, in which a survey was applied as a data collection technique to one hundred people from the establishment (service personnel, foreign tourists and employers). With the objective of determining the importance of the English language in the services offered and identifying the perception of foreign tourists regarding the use of the English language in interactive communication. It is concluded that on the part of employers there is a clear perspective towards their employees having a greater command of the English language for interactive communication with international guests. While from the perspective of foreign tourists it is necessary that, although they feel comfortable communicating in English during their stay at the Hotel, they require greater training in the use of the language.